Faktor - Faktor Yang Mempengaruhi Lamanya Mencari Kerja Bagi Tenaga Kerja Terdidik Di Kabupaten Penajam Paser Utara - Ani Agustini (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2017)
ABSTRACT Ani Agustini, 2017. Factors Affects on Finding Job’s Duration to People with Education in Kabupaten Penajam Paser Utara. Final Script for Economics of Economic and Business Faculty of Mulawarman University. Under guidance : (I) Mrs. Eny Rochaida, (II) Mrs. Diana Lestari.Purpose of the research is knowing about relation of education degree, age, and gender as Independent Variable to finding job’s duration of educational people in Kabupaten Penajam Paser Utara. The analysis method using Multiple Linier Regresi. To reach the purpose of this research using primary data, collected from interviewing sample as many as 100 respondents. Also use secondary data who is related with this research.Result of the research indicated that analysis Multiple Linier Regresi by simultaneous that education degree, age, and gender affect on duration of finding jobs, with test value is 45.682. Whereas, determine of coefficient value is 0.588 be significant on variable of education degree, age, and gender give 58.8 percent variation of finding job’s duration. And the 41.2 percent of finding job’s duration explained by another variable that not include in this research model. With significant value 0.000 for education degree and age, whereas 0.004 for gender which have less than 0.05, then the regression model be able to apply for predict the finding job’s duration or in other word the education degree, age, and gender affect on finding job’s duration in Kabupaten Penajam Paser Utara. Keywords: Education degree, age, gender, finding job’s duration